Inventorying emissions from nature in Europe (JOURNAL OF GEOPHYSICAL RESEARCH-ATMOSPHERES, 1999)
As part of the work of the Economic Commission for Europe of the United Nations Task Force on Emission Inventories, a new set of guidelines has been developed for assessing the emissions of sulphur, nitrogen oxides, NH,, CH,, and nonmethane volatile organic compounds (NMVOC) from biogenic and other natural sources in Europe. This paper gives the background to these guidelines, describes the sources, and gives our recommended methodologies for estimating emissions. We have assembled land use and other statistics from European or national compilations and present emission estimates for the various natural/biogenic source categories based on these. Total emissions from nature derived here amount to similar to 1.1 Tg S yr(-1), 6-8 Tg CH4 yr(-1), 70 Gg NH3 (as N) yr(-1), and 13 Tg NMVOC yr(-1). Estimates of biogenic NOx emissions cover a wide range, from 140 to 1500 Gg NOx (as N) yr(-1). In terms of relative contribution to total European emissions for different pollutants, then NMVOC from forests and vegetation are clearly the most important emissions source. Biogenic NOx emissions (although heavily influenced by nitrogen inputs from anthropogenic activities) are very important if the higher estimates are reliable. CH, from wetlands and sulphur from volcanoes are also significant emissions in the European budgets. On a global scale, European biogenic emissions are not significant, a consequence of the climate and size (7% of global land area) of Europe and of the destruction of natural ecosystems since prehistoric times. However, for assessing local budgets and for photochemical oxidant modeling, natural/biogenic emissions can play an important role. The most important contributor in this regard is undoubtedly forest VOC emissions, although this paper also indicates that NMVOC emissions from nonforested areas also need to be further evaluated. This paper was originally conceived as a contribution to the collection of papers arising as a result of the Workshop on Biogenic Hydrocarbons in the Atmospheric Boundary Layer, August 24-27, 1997. (Several papers arising from this workshop have been published in Journal of Geophysical Research, 103(D19) 1998.).
APS

Effect of habitat and age on variations in volatile organic compound (VOC) emissions from Quercus ilex and Pinus pinea (Atmospheric Environment, 1997)
A dynamic branch enclosure was used to measure emission rates of volatile organic compounds (VOCs) under field conditions from two common native Mediterranean species, Quercus ilex and Pinus pinea. In addition to a-pinene, B-pinene, sabinene, limonene and cineole, a suite of lesser known compounds were tentatively identified including cis- and trans-ocimene, cis- and trans-linalool oxide and sabinaketone. Emissions of isoprene from Quercus ilex were insignificant in comparison to those of the monoterpenes and were not detected from Pinus pinea. Variability in emission rates between two habitats, the forest and the dunes, were assessed for Quercus ibex. Temperature sensitivities of emissions and total summed emission rates from Quercus ilex were clearly related to environmental conditions. Emission rates from Pinus pinea showed great variability, but differences between normalised mean emission rates from mature forest and young plantation trees may be significant. Existing emission rate models were found to inadequately describe the observed data.

Screening of 18 Mediterranean plant species for volatile organic compound emissions (Atmospheric Environment, 1997)
Eighteen tree and shrub species were screened for emissions of isoprene and other volatile organic compounds (VOCs) at three locations at Castelporziano (Italy) using a bag-enclosure sampling method followed by GC analysis. Thirty emitted compounds were identified. Temperature sensitivity of emissions of monoterpenes varied between species. Strong temperature dependencies were found for isoprene emissions. For monoterpene-emitting plant species with greatest ground cover in the dunes and macchia habitats, α-pinene, β-pinene and sabinene appeared to be the most frequently and abundantly emitted compounds. Isoprene was the major emission from the shrub species screened in the forest. Emissions from four dominant plant species were scaled up to estimate total fluxes from the dunes and macchia over a daytime period. Species with greatest biomass but low emission rates made a substantial contribution to total emissions.